Prenatal diagnosis of a rare case of iniencephaly apertus - Mohsen, Mahy; El Sheikhah, Ahmed; Mohamed, Lamees; Ali, Sief El-Eslam; Michael, Armia; Radwan, Ahmad A.; Ali, Shymaa S.; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Iniencephaly is a rare neural tube defect that was firstly reported by Saint-Hilaire in 1836. Its incidence ranges from 0.1 to 10 in 10,000 deliveries with higher incidence in females. The most common features present iniencephaly are bifida at the cervical region, defect in the occipital bone and retroflexion of the head on the cervical spine. Here we report a case of a 24 years old second gravida with a history of consanguinity. She presented with a malformed fetus at 22 weeks gestation diagnosed by detailed ultrasonographic anatomy scan as iniencephaly apparatus. Termination of pregnancy was performed vaginally through medical induction by prostaglandins.